2017
DOI: 10.1111/pan.13084
|View full text |Cite
|
Sign up to set email alerts
|

Anterior rectus sheath blocks in children with abdominal wall pain due to anterior cutaneous nerve entrapment syndrome: a prospective case series of 85 children

Abstract: Anterior rectus sheath blocks using local anesthetics and steroids are safe and long-term successful in more than one-third of children suffering from abdominal pain due to anterior cutaneous nerve entrapment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Interestingly, two‐thirds of our patients reported more than 50% pain reduction for more than 4 weeks after diagnostic blocks. Siawash et al reported this phenomenon in patients with anterior cutaneous nerve entrapment and treated with anterior rectus sheath blocks. A possible explanation could be the interruption of the vicious circle of pain with a reset of the pain processing system .…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, two‐thirds of our patients reported more than 50% pain reduction for more than 4 weeks after diagnostic blocks. Siawash et al reported this phenomenon in patients with anterior cutaneous nerve entrapment and treated with anterior rectus sheath blocks. A possible explanation could be the interruption of the vicious circle of pain with a reset of the pain processing system .…”
Section: Discussionmentioning
confidence: 96%
“…Another explanation might be the use of ultrasound-guided injections instead of free-hand technique. An ultrasound-guided technique allows for a more accurate injection of the anesthetic agent, although short-term and long-term pain relief in adults did not differ between both techniques in lowquality studies [19,25,[34][35][36]. However, the ultrasound-guided technique might be useful to use in the pediatric population.…”
Section: Discussionmentioning
confidence: 98%
“…Initially, the preferred nonsurgical treatment is one or multiple injections with a local anesthetic agent (e.g. lidocaine or bupivacaine) into the trigger point, with or without corticosteroids and with or without ultrasound guidance [11,12,16,17,[24][25][26][27]. Surgical treatment, consisting of a neurectomy, should be considered if multiple injections with a local anesthetic agent are only successful for a short period of time [11,17,[19][20][21][22][23]28,29].…”
mentioning
confidence: 99%
“…Se han utilizado las inyecciones subfasciales guiadas por ecografía con 40 mg de lidocaína al 1% y 4 mg de dexametasona, y las inyecciones con 50 mg de lidocaína al 1% utilizando la técnica de manos libres y agregando 40 mg de metilprednisolona si se necesita tratamiento adicional [3][4][5][6][7][8][9] . El éxito de este tratamiento (con un número de inyecciones por paciente entre uno y siete) oscila entre el 38 y el 87% con una duración de seguimiento de cuatro semanas a 39 meses, según las series 3,5,9 . En nuestro caso optamos como primera estrategia de tratamiento por la inyección subfascial guiada por ecografía con 40 mg de lidocaína al 1% y 4 mg de dexametasona.…”
Section: Discussionunclassified